Focal Adhesion Kinase and Endothelial Cell Apoptosis - Lu, Qing (2011)
Focal adhesion kinase is a key component of cell-substratum adhesions, known as focal adhesion complexes. Growing evidence indicates that FAK is important in maintenance of normal cell survival and that disruption of FAK signaling results in loss of substrate adhesion and anoikis (apoptosis) of anchorage-dependent cells, such as endothelial cells. Basal FAK activity in non-stimulated endothelial cells is important in maintaining cell adhesion to integrins via PI3 kinase/Akt signaling. FAK activity is dependent upon small GTPase signaling. FAK also appears to be important in cardiomyocyte hypertrophy and hypoxia/reoxygenation-induced cell death. This review summaries the signaling pathways of FAK in prevention of apoptosis and the role of FAK in mediating adenosine and homocysteine-induced endothelial cell apoptosis and in cardiovascular diseases.